The Implementation of the Cascading Method in Post-COVID-19 English Language Learning at SDN 3 Timpag Tabanan - Kuntariati, Utik (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
As of COVID-19, instruction methods are once again being optimized through enticing education, which has been going strong for the past year. Every institution of higher learning that exists in Indonesia, from elementary schools to universities, is targeted by offline learning. SDN 3 Timpag Kabupaten Tabanan is the only primary school now operating under an offline curriculum. But as of right now, SDN 3 Timpag is experiencing a few setbacks, particularly when it comes to the implementation of the teaching method for students who previously studied using the online learning method. The research uses a qualitative approach as a method of analysis. The term